The Effect of Common Herbicides on Root Tip Cells of Trigonella foenum-graecum (Fenugreek) - Devi, Hijam Ranakumari; Loitongbam, Toreena (Journal of Research in Science and Engineering, 2026)
Herbicides are chemicals used to manipulate or control undesirable vegetation. For study Maleic hydrazide were chosen as herbicide because it is applied to onions in the field at a rate of 2.2kg/ha when the bulbs are mature. It is widely known as plant growth regulator, used to suppress growth and induce dormancy in some crops and mostly used to reduce sprouting in stored crops. In the present investigation, the seeds of Trigonella foenum graceum were treated with four different concentrations (10−1, 10−2, 10−3, 10−4) of maleic hydrazide to observe the cytological effect on them. The treatment was given at the seed level. Various abnormalities were noticed at cytological level in different concentrations. Fragmented nuclear material, Sticky metaphase, Sticky Anaphase, Vacuolated cells, Elongated cells, Binucleated, Disrupted Cells were the most frequent abnormalities. The decrease in germination rate was observed in 10−3. Maximum abnormalities were observed in 10−3 and 10−4.